Digital Official Letter Management Using E-Buddy Sidoarjo Application: Pengelolaan Surat Resmi Digital Menggunakan Aplikasi E-Buddy Sidoarjo - Albab, Mukhammad Ulil; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The rise of digital technology has revolutionized local governance by enhancing efficiency and transparency. Specific Background: In this context, the E-Buddy application facilitates the digital management of official correspondence, yet its effectiveness has not been thoroughly examined. Knowledge Gap: Current literature lacks a detailed analysis of the communication dynamics and bureaucratic structures affecting the success of such digital systems. Aims: This study investigates the implementation of the E-Buddy application, emphasizing communication, resource allocation, executor disposition, and bureaucratic structure. Results: Findings reveal that the application's effectiveness is undermined by limited feature utilization and insufficient adherence to standard operating procedures (SOPs), resulting in miscommunication and inefficiencies. Novelty: The research underscores the importance of effective communication and structured SOPs in optimizing digital systems in governance. Implications: The study recommends enhancing training and establishing clear SOPs to improve implementation outcomes and contribute to more effective governance. Highlights : Effective communication is crucial for successful implementation. Insufficient adherence to SOPs hampers operational efficiency. Training and support enhance user engagement and application effectiveness. Keywords: Digital Governance, E-Buddy Application, Implementation, Communication, Bureaucratic Structure